Morphological Characterization and Diversity of T. Aman Rice Germplasm of Bangladesh - Ahmed, MS; Rashid, ESMH; Akter, N; Khalequzzaman, M (Bangladesh Rice Journal, 2019)
Fifty-four T. Aman rice landraces were studied for 11 morphological and yield contributing characters at Bangladesh Rice Research Institute during T. Aman 2016 season. The largest variation was observed for yield per hill with 53.6% CV, followed by 1000 grain weight (29.9), number of effective tillers per hill (22.8), culm diameter (18.8), leaf width (18.4), leaf length (18.1) and days to maturity (6.7) respectively. The longest leaf was recorded as 82.2 cm and that of culm diameter as 7.57 mm, grain length as 7.2 mm and LB ratio as 3.48. The shortest days to maturity (110 days) was observed in Kajal lata and plant height (86.6 cm) in Haijam. Indursail possessed the longest panicle (31.6 cm) and the highest yield per hill (24.3 g). Based on D2 values, all the germplasm were grouped into 15 clusters using Mahalonobis D2 statistic. The maximum numbers of germplasm (7) were grouped into the clusters IV with VI, whereas clusters III and XIII contained the minimum (1). The highest intra-cluster distance (1.0) was found in cluster II and the lowest (0.0) in clusters III and XIII, respectively. The inter-cluster D2 values ranged from 19.2 to 0.6 indicating wide range of diversity among the germplasm. Cluster XIII showed the highest leaf length (82.2 cm) and culm diameter (6.5 mm), cluster IX the highest effective tillers per hill (13), cluster II the lowest days to maturity (117), cluster XV the highest grain length (6.1 mm) and cluster I the highest grain LB ratio (2.97), while cluster VIII showed the highest yield per hill (22.0 g), panicle length (28.8 cm) and 1000 grain weight (25.2 g), respectively. Finally, the germplasm under clusters VIII may be selected for crossing with the germplasm from clusters XIII, IX, II, XV and I for developing high yielding varieties with improved panicle length, effective tillers per hill, growth duration and grain type. Bangladesh Rice j. 2018, 22(2): 13-22